Second-step lectotypification of the name Capparis parviflora J. D. Hooker & Thomson (Capparaceae) - Kottaimuthu, Ramalingam (Phytotaxa, 2018)
The genus Capparis Linnaeus (1753: 503) has about 600 species (Zhang & Tucker 2008), distributed in tropical and subtropical regions worldwide and some in temperate regions (Fisci 2015). There are 30 species of Capparis in India (Viswanathan 2000), of these Capparis fusifera Dunn (1914: 377), Capparis grandiflora Wallich ex J. D. Hooker & Thomson (1872: 174), Capparis kollimalayana M.B. Viswanathan (2000: 245), Capparis nilgirinesis Subba Rao, Kumari & V. Chandras. (1981: 146), and Capparis rheedii Candolle (1824: 246) are endemic to Peninsular India (Sundararaghavan, 1993, Singh et al. 2015).